Tissue reaction to endométhasone sealer in root canal fillings short of or beyond the apical foramen - Suzuki, Patrícia; Souza, Valdir de [UNESP]; Holland, Roberto [UNESP]; Gomes Filho, João Eduardo [UNESP]; Murata, Sueli Satomi [UNESP]; Dezan Junior, Eloi [UNESP]; Passos, Thiago Rodrigues dos (FapUNIFESP (SciELO), 2011)
Objective: This study evaluated the response of periapical tissues to the endodontic sealer Endométhasone in root canal fillings short of or beyond the apical foramen. Material and Methods: Twenty root canals of premolars and incisors of 2 mongrel dogs were used. After coronal access and pulp extirpation, the canals were instrumented up to a size 55 K-file and the apical cemental barrier was penetrated with a size 15 K-file to obtain a main apical foramen, which was widened to a size 25 K-file. The canals were irrigated with saline at each change of file. The root canals were obturated either short of or beyond the apical foramen by the lateral condensation of gutta-percha and Endométhasone, originating 2 experimental groups: G1: Endométhasone /short of the apical foramen; G2: Endométhasone/beyond the apical foramen. The animals were killed by anesthetic overdose 90 days after endodontic treatment. The individual roots were obtained and serial histological sections were prepared for histomorphological analysis (H&E and Brown & Brenn techniques) under light microscopy. The following parameters were examined: closure of the apical foramen of the main root canal and apical opening of accessory canals, apical cementum resorption, intensity of the inflammatory infiltrate, presence of giant cells and thickness and organization of the apical periodontal ligament. Each parameter was scored 1 to 4, 1 being the best result and 4 the worst. Data were analyzed statistically by the Wilcoxon nonparametric tests (p=0.05). Results: Comparing the 2 groups, the best result (p<0.05) was obtained with root canal filling with Endométhasone short of the apical foramen but a chronic inflammatory infiltrate was present in all specimens. Conclusions: Limiting the filling material to the root canal space apically is important to determine the best treatment outcome when Endométhasone is used as sealer.
Keywords: Biocompatibility test; Endométhasone; Root canal therapy